2022
DOI: 10.1177/16094069221131168
|View full text |Cite
|
Sign up to set email alerts
|

Research Participation in Substance Use Disorder Trials: Design and Methods of a Multi-Site Nested Qualitative Study

Abstract: Background Given the health and social harms of problematic substance use, randomized controlled trials (RCTs) are critical in developing and testing pharmacotherapies for substance use disorders. However, substance use RCTs can be challenging to conduct, considering the social and structural barriers to participating in research among people with substance use disorders (PSUD), including stigma, poverty, and criminalization—factors that can shape trial recruitment, enrollment, protocol adherence and study ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…S evere infections are prevalent in people who inject drugs (PWID), and studies have shown that co-occurring opioid and methamphetamine use is increasingly prevalent 1 and associated with poor health outcomes, including infectious complications and risky injection behaviors, 2 as well as lower rates of linkage to outpatient buprenorphine treatment compared with opioid use alone. 3 In patients who use opioids and are hospitalized for infectious complications of injection drug use, there is limited evidence that stimulant use is associated with worse outcomes in terms of infection treatment and retention in care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S evere infections are prevalent in people who inject drugs (PWID), and studies have shown that co-occurring opioid and methamphetamine use is increasingly prevalent 1 and associated with poor health outcomes, including infectious complications and risky injection behaviors, 2 as well as lower rates of linkage to outpatient buprenorphine treatment compared with opioid use alone. 3 In patients who use opioids and are hospitalized for infectious complications of injection drug use, there is limited evidence that stimulant use is associated with worse outcomes in terms of infection treatment and retention in care.…”
mentioning
confidence: 99%
“…However, we agree and acknowledge the importance of using longer, multidimensional, patient-centered, patient-reported experience assessments of this construct in future longitudinal studies in patients receiving opioid agonist therapies. Therefore, we conducted an ancillary nested qualitative study 2 to gain an in-depth understanding of the multidimensional perspectives of participants, as well as clinicians, regarding the interventions and their participation in the (Optimizing Patient Centered-care: A Pragmatic Randomized Control Trial Comparing Models of Care in the Management of Prescription Opioid Misuse) study. We hoped that such a qualitative approach would provide complementary and richer data pertaining to participants' perspectives on opioid agonist therapies, which hopefully might contribute to future development of relevant measure.…”
mentioning
confidence: 99%